Early events following bovine leukaemia virus infection in calves with different alleles of the major histocompatibility complex DRB3 gene - Forletti, Agustina (2020)
Cattle maintaining a low proviral load (LPL) status after Bovine Leukemia Virus (BLV) infection have been recognized as BLV controllers, and non-transmitters to uninfected cattle in experimental and natural conditions. LPL has been associated with host genetics, mainly with BoLAclass II DRB3 gene. The aim of this work was to study the kinetics of the BLV and the host response in Holstein calves carrying different BoLA-DRB3 alleles. Twenty BLV free calves were inoculated with infected lymphocytes. Two calves were maintained uninfected as controls. Proviral load, total leukocyte and lymphocyte counts, anti-BLVgp51 titers and BLVp24 expression were determined in blood samples at various times post inoculation (dpi).Proviral loadpeaked at 30 dpi in all animals. It declined steadily from seroconversion (38 dpi) to the end of the study (178 dpi) in calves carrying resistance-associated allele (*0902), while it was maintained at elevated levels in calves with *1501 or neutral alleles after seroconversion. Leukocyte and lymphocyte counts and BLVp24 expression did not significantly differ between genetic groups. Animals with <20 proviral copies/30 ng DNA at 178 dpi or < 200 proviral copies at 88 dpi were classified as LPL, while calves with levels above these limits were considered as high proviral load (HPL) profile. All 6 calves with*1501 allele progressed to HPL, while LPL was attained by 6/7 (86%) and 2/6 (33%) of the calves with *0902 and neutral alleles respectively. One calf with both *0902 and *1501 developed LPL. This is the first experimental induction of LPL profile in cattle.